2007
DOI: 10.1111/j.1460-9568.2007.05364.x
|View full text |Cite
|
Sign up to set email alerts
|

PKCε induces astrocyte stellation by modulating multiple cytoskeletal proteins and interacting with Rho A signalling pathways: implications for neuroinflammation

Abstract: Despite the importance of stellation to maintain astrocyte functionality, the intracellular signals controlling morphology in these cells are poorly characterized. Our goal was to examine the implication of protein kinase C epsilon (PKCepsilon) in astrocyte stellation. We found that the morphological transformation of astrocytes induced by exposure to the pro-inflammatory agent lipopolysaccharide is enhanced by adenoviral expression of wild-type PKCepsilon, and that activation of PKCepsilon is sufficient to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…RhoA, another actin polymerization mediator that mediates LPS-induced astrocyte migration (Sato et al, 2011) and MKL1 activation in various cell types (Smith et al, 2013), was also found to affect Slc1a2 gene transcription in a transcriptome analysis of RhoA kinase inhibitor-treated astrocytes . On the contrary, the activation of astrocytic RhoA with injury or chemical insults has been shown to play an adverse role in suppressing astrocyte stellation (Burgos et al, 2007) and exacerbating the inflammatory response (Dusaban et al, 2013) in addition to increasing astrocyte apoptosis (Miñambres et al, 2006). In the present study, astrocytic GAP43 appears to modulate astrogliosis toward beneficial features in various aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RhoA, another actin polymerization mediator that mediates LPS-induced astrocyte migration (Sato et al, 2011) and MKL1 activation in various cell types (Smith et al, 2013), was also found to affect Slc1a2 gene transcription in a transcriptome analysis of RhoA kinase inhibitor-treated astrocytes . On the contrary, the activation of astrocytic RhoA with injury or chemical insults has been shown to play an adverse role in suppressing astrocyte stellation (Burgos et al, 2007) and exacerbating the inflammatory response (Dusaban et al, 2013) in addition to increasing astrocyte apoptosis (Miñambres et al, 2006). In the present study, astrocytic GAP43 appears to modulate astrogliosis toward beneficial features in various aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytic GAP43 knockdown augmented astrogliosisinduced microgliosis and inhibited axonal plasticity Next, we investigated the role of astrocytic GAP43 on the microgliosis and neuronal plasticity, as the actin reorganization is known to be involved in the reactive astrocyte-regulated immune response, synaptic plasticity, and neuronal survival (Tancredi et al, 2000;Haber et al, 2006;Burgos et al, 2007;Strehl et al, 2014). We applied ACM derived from LPS-treated primary astrocytes transfected with Scr or Gap43 siRNA onto primary rat microglia and cortical neurons (Fig.…”
Section: S41-phosphorylated Gap43 Mediates Astrocytic Plasticitymentioning
confidence: 99%
“…Previously, it was demonstrated that RhoA negatively regulated astrocyte stellation (Suidan et al, 1997;Abe and Misawa, 2003;Chen et al, 2006;Burgos et al, 2007), migration (Höltje et al, 2005), and the IL-1␤-induced reactive astroglial phenotype (John et al, 2004). RhoA activation was, however, required for Thy-1-induced morphological changes in astrocytes that resembled those in brain injuries (Avalos et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A pro-inflammatory agent lipopolysaccharide (LPS) that induces astrocyte stellation has enhanced activity in the presence of PKCε. This effect is blocked by expression of constitutively active Rho A, demonstrating that PKC activity is important for inactivating Rho A dependent pathways [21]. LPS signaling mechanisms are unclear but recently it was shown that TRAM (Toll-like receptor 4 adaptor molecule) is directly phosphorylated by PKCε on Ser 16 .…”
Section: Lipid Activation Signalsmentioning
confidence: 99%